The impact of international law in Latin America´s domestic legislations. The access to public information and its scope - Negro Alvarado, Dante M. (REVISTA ELECTRONICA IBEROAMERICANA, 2022)
This paper aims to establish the correct scope of the right of access to public information through the conceptualisation of its fundamental elements. An important aspect will be to understand the correct application of the principle of maximum disclosure (central axis on which this topic is based) in harmony with the regime of exceptions as defined in the Inter-American Model Law 2.0. Indeed, the right of access to public information is not unlimited. There are circumstances in which restrictions may be placed on it. Since all fundamental rights have the same hierarchy, in the event of a collision between them, the solution is not simply to make some prevail over others, but to resolve it on the basis of the technique of weighting. In this sense, the Model Law 2.0 attempts two things: to give the widest possible scope to the right of access to public information, guaranteeing the adequate provision of information in such a way that it is useful and serves its essential purpose, and to guarantee the effective concordance in the application of the different interests and rights that may be involved in a specific situation.
Keywords: Organization of American States; Inter-American Model Legislation 2.0; Access to Public Information; Subject entities; Exceptions; Principle of maximum disclosure